Late Pleistocene sedimentary environment and reverse faulting along the Chugaryung Fault in the central Korean Peninsula: a case study on the Cheorwon Basin - Shin, Seungwon; Cheon, Youngbeom; Choi, Jeong-Heon; Cheong, Daekyo; Choi, Seung-Yup; Lim, Hyoun Soo; Bae, Hankyung; Lee, Hee-Kwon (Geosciences journal (Seoul, Korea), 2020)
The Cheorwon area of South Korea has several records of the Quaternary faulting along the Chugaryung fault system and volcanic activity (Hantangang River Basalt). The most recent faulting event occurred along a segment of the Wangsukcheon fault (ca. 210 ka). In this study, a 5-m-deep trench was examined at the northern end of the Cheorwon Plain. The formation mechanism(s) and characteristics of local sediments as well as the timing of the Quaternary faults observed in the lower sections were analyzed. The sediments are very fine-grained, with a sand content of less than 5%. Soil wedge structures indicate that the sediments were affected by an ice-age environment. Some stratification and our analyses suggest that the sediments were formed on a floodplain. The ages of the sediments range from 150 to 130 ka, based on quartz optically-stimulated luminescence (OSL) dating. The absence of sediments younger than 100 ka is likely attributable to a change to sedimentary environments where erosion processes are dominant, with sediments being removed to the Hantangang River area. Meanwhile, a N-S-striking fault, dipping 30° eastward, cut across the sediments during 140–130 ka. This study provides important information on Quaternary sedimentary environment nearby the Hantangang River area, but also the introduction of the Quaternary fault into Chugaryung fault system, which has been lacking to data.